Elucidating tobacco smoke-induced craniofacial deformities: Biomarker and MAPK signaling dysregulation unraveled by cross-species multi-omics analysis - Yuxin Lin; Hao Li; Shukai Zheng; Rui Han; Kusheng Wu; Shijie Tang; Xiaoping Zhong; Jiasheng Chen (Ecotoxicology and Environmental Safety)
Tobacco smoke (TS), particularly secondhand and thirdhand smoke, poses a pervasive and intractable environmental hazard that promotes teratogenesis and the progression of craniofacial malformations, although the underlying mechanisms remain elusive. Using zebrafish larvae as a model, our research demonstrated a correlation between the increasing concentration of cigarette smoke extract (CSE) and the severity of craniofacial malformations, supported by Alcian blue staining and histological assessments. Through a combined mRNA-miRNA analysis and quantitative real-time PCR, we identified miR-96–5p, miR-152, miR-125b-2–3p, and miR-181a-3–3p as pivotal biomarkers in craniofacial cartilage development. Functional analyses revealed their association with the MAPK signaling pathway, oxidative stress (OS), and cell development, highlighting MAPK as a crucial mediator. Single-cell transcriptomics further disclosed aberrant MAPK activation in mesenchymal cells. Subsequent investigations in human embryonic palatal mesenchymal (HEPM) cells confirmed similar patterns of growth inhibition, apoptosis, and OS, and emphasized the cross-species consistency of these biomarkers and the over-activation of the MAPK signaling pathway. A comprehensive tri-omics analysis of HEPM cells identified pivotal genes, proteins, and metabolites within the MAPK pathway. This groundbreaking cross-species multi-omics study unveils novel biomarkers and MAPK pathway perturbations linked to TS-induced craniofacial developmental toxicity, promoting innovative clinical prediction, diagnosis, and interventional strategies to tackle TS-induced craniofacial malformations.